Lethal Concentration (LC50) of Myristicin (Myristica fragrans Houtt) on Larva Aedes aegypti Instar III - Arrizqiyani, Tanendri; Mardiana, Ummy; Hidana, Rudy; Nurhamidah, Siti (EKSAKTA: Journal of Sciences and Data Analysis, 2024)
Myristicin is an active substance that can be found in nutmeg plants. The purpose of this study was to determine the LC50 myristicin against larval instar III of Aedes aegypti. The method used is the experimental method. The samples used were myristicin isolates with varying concentrations of 5 ppm, 10 ppm, 15 ppm, and 20 ppm against Aedes aegypti instar III larvae. The parameters observed were LC50 Aedes aegypti larvae for 24 hours. The results obtained are based on calculations using IBM SPSS Statistics 22.0 using the probit formula it is known that LC50 isolate myristicin which can kill larvae at 12 hours is 10 ppm and the positive control is 10 ppm. These results are better when compared with results in other studies with LC50 of 111,002 ppm and positive control at 24 hours. Based on the results of research that has been done, it can be concluded that the LC50 isolate of Myristicin (Myristica fragrants Houtt) against Aedes aegypti Instar III larvae at the 12th hour is 10 ppm.